2013
DOI: 10.1016/j.foodchem.2012.09.100
|View full text |Cite
|
Sign up to set email alerts
|

Natural occurrence of deoxynivalenol in wheat from Paraná State, Brazil and estimated daily intake by wheat products

Abstract: The occurrence of deoxynivalenol (DON) was evaluated in 113 wheat samples from the northern and central/southwestern regions of Paraná State, Brazil during the 2008 and 2009 growing seasons, and this rate of occurrence was used to estimate the DON dietary exposure. The DON determination was carried out by an indirect competitive enzyme-linked immunosorbent assay. DON was detected in 66.4% samples at levels ranging from 206.3 to 4732.3 μg/kg (mean 1894.9 μg/kg). The estimated daily intake (EDI) of DON through b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 74 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…Overall, the debranning time of 15 s was the most effective in the DON reduction, approximately 500 µg/kg, when all samples were considered (Figure 1). According to Santos et al (2013), the mean DON content in wheat from Paraná State was 1894.9 µg/kg. Savi et al (2016) analyzed wheat samples from Southern Brazil and reported that the bran fraction had the highest mean concentration of DON (2,278 µg/ kg), followed by milled wheat and finished flour (1895 µg/ kg and 1,305 µg/kg).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the debranning time of 15 s was the most effective in the DON reduction, approximately 500 µg/kg, when all samples were considered (Figure 1). According to Santos et al (2013), the mean DON content in wheat from Paraná State was 1894.9 µg/kg. Savi et al (2016) analyzed wheat samples from Southern Brazil and reported that the bran fraction had the highest mean concentration of DON (2,278 µg/ kg), followed by milled wheat and finished flour (1895 µg/ kg and 1,305 µg/kg).…”
Section: Discussionmentioning
confidence: 99%
“…The male and female average weight were 3.3 and 3.2 kg for infants aged one week, 4.5 and 4.2 kg for one month, 7.9 and 7.3 kg for six months, and 9.6 and 8.9 kg for 12 months [ 30 ]. The EDI of AFM 1 was calculated according to the following formula and expressed in ng/kg of body weight/day (ng/kg b.w./day) [ 55 ]. …”
Section: Methodsmentioning
confidence: 99%
“…Flour is the fraction that contributes the most to the daily intake of DON in Southern Brazil, representing 89.6% of the provisional maximum tolerable daily intake (Savi et al, 2016). According to Santos et al (2013), the average intake of the inhabitants of Londrina City in northern Paraná State (Brazil) was 0.79 μg/kg body weight for bread and 0.35 μg/kg body weight for pasta. The total estimated daily intake of DON was 1.13 μg/kg, which is above the provisional tolerable daily maximum intake of 1 μg/kg body weight, established by FAO/WHO Expert Committee (JECFA, 2001).…”
Section: Discussionmentioning
confidence: 99%